Public Knowledge About the Use of Toga as Food to Improve Health - Aseptianova Aseptianova; Laura Indriani (Syntax Idea, 1954)
Toga is a cultural or maintenance plant that is natural and easy to obtain and easy to grow in the yard of the house. Toga is used as family medicine, one of which can also be used by processing toga as food. The purpose of this study is to find out how public knowledge after being given information about the use of toga as food to improve health. This study used quantitative descriptive method with pre test &; post test data collection. Data was collected through interviews with the community, and supported by documentation. The results of this study stated that public knowledge about the use of toga as food to improve health in Biology subjects on the subject of Biodiversity, Toga as food to improve health that the calculated t value (10.850) with a significant value of 0.000 is greater than 0.05. That is, there is an increase in public knowledge about efforts to improve health through the use of toga as food